2020
DOI: 10.1101/2020.10.22.20217984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Economic Benefits of COVID-19 Screening Tests

Abstract: We assess the economic value of screening testing programs as a policy response to the ongoing COVID-19 pandemic. We find that the fiscal, macroeconomic, and health benefits of rapid SARS-CoV-2 screening testing programs far exceed their costs, with the ratio of economic benefits to costs typically in the range of 4-15 (depending on program details), not counting the monetized value of lives saved. Unless the screening test is highly specific, however, the signal value of the screening test alone is low, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Our findings confirm those of other investigators that home-based rapid testing can have a dramatic effect in reducing transmission and COVID-19 mortality at a justifiable cost, 1,32 with testing frequency a key component to why this broad testing strategy is so effective. Factors currently in play that could worsen the pandemic -a slow start to roll out of widespread vaccination, "pandemic fatigue" regarding social distancing and mask wearing, and emergence of variants that are more easily transmissible -only underscore the importance of frequent rapid testing as a strategy to reduce the number of new cases.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings confirm those of other investigators that home-based rapid testing can have a dramatic effect in reducing transmission and COVID-19 mortality at a justifiable cost, 1,32 with testing frequency a key component to why this broad testing strategy is so effective. Factors currently in play that could worsen the pandemic -a slow start to roll out of widespread vaccination, "pandemic fatigue" regarding social distancing and mask wearing, and emergence of variants that are more easily transmissible -only underscore the importance of frequent rapid testing as a strategy to reduce the number of new cases.…”
Section: Discussionsupporting
confidence: 90%
“…One strategy receiving less formal attention is the high-frequency use of low-cost, rapid, home-based antigen testing for SARS-CoV-2 with self-enforced isolation for those who obtain a positive result. [1][2][3][4][5] Advocates point to the potential advantages: prevention by isolation; focusing on "infectiousness" rather than "infection"; and reducing strain on laboratories that must conduct viral polymerase chain reaction (PCR)-based diagnostic testing. [6][7][8] Critics note that such an approach risks poor uptake and adherence, frequent false negatives leading to unfounded reassurance, and frequent false positives resulting in needless isolation and lost work productivity.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 7 Such studies have also suggested limited benefit from using tests with greater sensitivity for detecting SARS-CoV-2. 7 , 10 The findings of our current real-world study largely support the conclusions of the modeling studies.…”
Section: Discussionsupporting
confidence: 79%
“…Bergemann et al (2018) study incentive compatibility in a market for information. Atkeson et al (2020) point out in the context of COVID-19 testing that the precision of the post-test posterior information enhances compliance with quarantine measures.…”
Section: Discussionmentioning
confidence: 99%